2017
DOI: 10.12691/jfs-5-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Food Insecurity among Women Aged 18-49 Years in Kampala Slums Uganda; A Mixed Methods Study

Abstract: While much focus has been put on rural household food insecurity, with increasing urbanisation leading to urban slum formation, food insecurity is potentially on the rise particularly among women of reproductive age (WRA). We determined the prevalence and factors associated with food insecurity among women aged 18-49 years in Makindye slums of Kampala capital city, Uganda. In a community based cross-sectional study, we recruited a random sample of 573 women aged 18-49 years, resident in the slums for at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
5
14
1
Order By: Relevance
“…This may compromise their ability to meet recommended dietary intake and therefore increasing their risk for underweight. This is supported by findings of a recent study that showed a high prevalence (88.5%) of food insecurity among women dwelling in one of the divisions of the most urbanized areas of the capital city Kampala [ 48 ]. The rapid increase in the urban settlements has also led to sanitation challenge and environmental degradation [ 22 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This may compromise their ability to meet recommended dietary intake and therefore increasing their risk for underweight. This is supported by findings of a recent study that showed a high prevalence (88.5%) of food insecurity among women dwelling in one of the divisions of the most urbanized areas of the capital city Kampala [ 48 ]. The rapid increase in the urban settlements has also led to sanitation challenge and environmental degradation [ 22 ].…”
Section: Discussionsupporting
confidence: 80%
“…In Uganda, most agricultural production occurs in rural areas which contributes greatly to rural food availability and access [ 41 ]. Uganda is experiencing rapid urbanization that has led to the poorest and highly vulnerable people to settle in poorly organized informal urban areas [ 22 , 48 ] . Despite the availability of regular food supply in urban areas, the urban poor households that make up the majority of the urban population have limited access to sufficient and nutritious food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may compromise their ability to meet recommended dietary intake and therefore increasing their risk for underweight. This is supported by ndings of a recent study that showed a high prevalence (88.5%) of food insecurity among women dwelling in one of the divisions of the most urbanized areas of the capital city Kampala [48]. The rapid increase in the urban settlements has also led to sanitation challenge and environmental degradation [22].…”
Section: Discussionmentioning
confidence: 79%
“…In Uganda, most agricultural production occurs in rural areas which contributes greatly to rural food availability and access [41]. Uganda is experiencing rapid urbanization that has led to the poorest and highly vulnerable people to settle in poorly organized informal urban areas [22,48].…”
Section: Discussionmentioning
confidence: 99%